Small heat shock proteins as modulators of cell death in Plasmodium falciparum parasites and its human host - Timothy, Francisca Magum; Zininga, Tawanda (Frontiers in Cell Death, 2023)
Plasmodium falciparum, the predominant cause of severe malaria, thrives within both poikilotherm mosquitoes and homeotherm humans, navigating challenging temperature shifts during its life cycle. Survival in such varying environments necessitate the development of robust mechanisms, including a sophisticated protein folding system to mitigate proteopathy. The parasite needs to control the survival of its host cells which affects its chances of development and propagation. Central to this system are heat shock proteins (Hsps), among which small Hsps (sHsps) play pivotal roles in maintaining proteostasis (protein homeostasis). In both humans and P. falciparum, numerous sHsps have been identified, making them attractive candidates as biomarkers for diagnostic and drug development strategies. Evidence is accumulating suggesting that these sHsps participate in cell death processes, potentially influencing disease pathogenesis. Despite their significance, the precise functions of sHsps in P. falciparum’s adaptation to stress conditions remains largely unknown. Comparative structural analysis of sHsps between human and P. falciparum reveals species-specific variations. Despite conserved tertiary structures, unique motifs are found in parasite sHsps which may modulate specialised chaperone functions. This review discusses the conserved and distinctive motifs of sHsps from the human host and the parasite, offering insights into shared and unique attributes. These findings illuminate the potential for species-specific targeting of sHsps, as players in cell death processes that may foster innovative biomarker identification approaches. As malaria continues to ravage Sub-Saharan Africa, understanding the molecular intricacies guiding parasite survival are essential in the development of interventions with heightened efficacy against this global health crisis.